2019
DOI: 10.1002/ajhb.23372
|View full text |Cite
|
Sign up to set email alerts
|

Sitting/lying time is associated with waist‐to‐hip increase but not with body weight increase or blood cardiovascular risk factors changes in adult women living in social vulnerability: A 2‐year longitudinal study

Abstract: Objective: The present study aimed to determine whether physical activity and energy intake are associated with the anthropometric and blood cardiovascular risk factors alterations in women living in social vulnerability for a period of 2 years. Methods:The study was carried out with women residing in the outskirts of Maceió-AL, aged between 19 and 45 years. We characterized the socioeconomic and biochemical profile (glucose, insulin, and blood lipids) at the beginning and at the end of the study. Anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Fujii et al, 2021 investigated the clinical effect of sedentary behavior on chronic kidney disease and showed that sedentary behavior was a significant predictor of the incidence of proteinuria in men [ 42 ]. Of the remaining six studies, three showed that sedentary behavior was not associated with HDL, LDL, triglycerides, and serum insulin [ 30 , 32 , 43 ]. Two studies showed no association between different sedentary behaviors (e.g., television viewing, computer use, and driving) and self-reported prevalence of hypertension [ 31 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujii et al, 2021 investigated the clinical effect of sedentary behavior on chronic kidney disease and showed that sedentary behavior was a significant predictor of the incidence of proteinuria in men [ 42 ]. Of the remaining six studies, three showed that sedentary behavior was not associated with HDL, LDL, triglycerides, and serum insulin [ 30 , 32 , 43 ]. Two studies showed no association between different sedentary behaviors (e.g., television viewing, computer use, and driving) and self-reported prevalence of hypertension [ 31 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The longitudinal studies conducted by Staiano et al, 2018 and Silva et al, 2019 found that there was no significant relationship between sedentary behavior and adiposity indicators when it was measured by X-ray and ultrasound scanners [ 12 , 37 ]. Conversely, van de Laar et al, 2014 and Vieira et al, 2020 identified a significant longitudinal association between sedentary behavior and adiposity indicators, which was measured using simple tools (tape measure, electronic scales) [ 29 , 43 ]. The findings imply that future studies need to distinguish the different dimensions of adiposity indicators and use standardized measures to assess the relationship between sedentary behavior and adiposity indicators.…”
Section: Discussionmentioning
confidence: 99%